My notes from the 2nd ARC reports - Pavneet Singh. S (New Delhi : Unique Publishers India Pvt Ltd, 2022)
This book comprehensively covers the 2nd ARC Reports from the perspective of civil services mains examination. The students can rely upon the notes here for their exam because they are written in a user-friendly format that enhances learner retention. The distinctive feature of this book is that it contains a context explaining why the 2nd ARC Reports made certain recommendations, rather than just giving compilation of recommendations that makes no sense without a context. This book enables a reader to contextualize the problem related to Governance structures in India and analyze the presented solution. Doing so provides the students with a ready reckoner of content for 23 topics in the civil services mains examination that can be only prepared from the 2nd ARC Reports.
Keywords: Competitive Exam; ARC reports